PENTINGNYA KUALITAS PELAYANAN JASA DALAM KEPUASAN KONSUMEN DI OUTLET MIXUE ICE CREAM AND TEA MULYOSARI SURABAYA - Alfredo, Matheus (Universitas Widya Kartika Surabaya, 2024)
This research aims to determine the importance of service quality in satisfying consumers at the Mixue Ice Cream and Tea Mulyosari outlet, Surabaya. Mixue Ice Cream & Tea is a franchise company that sells soft serve ice cream and tea drinks originating from Zhengzhou, Henan, China, and was founded on June 16 1997. By 2023, Mixue has 21,581 outlets spread across China and at least 12 other countries in Asia-Pacific. Mixue started entering the Indonesian market in 2020 and by 2023 it has spread to approximately 10,000 outlets. This research uses a qualitative approach with data collection techniques through interviews with informants and direct observation at the research location. The research results show that the service provided by Mixue employees in Mulyosari is good and in accordance with company standards, although there are still several shortcomings that need to be corrected, such as the lack of employee sensitivity to consumer confusion and inadequate facilities. The conclusion of this research is that service quality is very influential in creating consumer satisfaction. Researchers suggest that Mixue improve existing services and facilities to better satisfy its consumers. Apart from that, education and training for employees on how to provide good service needs to be implemented to maintain and improve the quality of the services provided